Implementation of Sustainable Business Models in Management: A Systematic Review of Approaches and Solutions - Anfi, Dieva Zahrohtu; Wahyudi, Eko Juni; Masruroh, Putria Dewi; Pratesa, Dimas Putri Mega; Pratiwi, Nova Rizca (Universitas Negeri Makassar, 2025)
The implementation of sustainable business models is increasingly considered important in the business world which focuses on environmental, social and economic sustainability. This study aims to review the existing literature on the application of sustainable business models in management with a focus on the approaches applied and solutions adopted by organizations to address sustainability-related challenges. The research method used is Systematic Literature Review (SLR) , where relevant articles are collected through searches in several leading databases. The research results show that sustainable business models are more often implemented with the Triple Bottom Line (TBL) approach , which includes economic, social and environmental aspects in business strategy. The main obstacles faced by companies are limited resources, uncertainty in measuring impact, and organizational cultural resistance to change. Solutions identified include collaboration between the public and private sectors, the implementation of environmentally friendly technologies, and training to increase understanding of sustainability among stakeholders.